Digital games for entrepreneurial learning, innovation and creativity: examples and evaluation criteria. Issue 3 (1st January 2012) - Tragazikis, Panagiotis; Kirginas, Sotiris; Gouscos, Dimitris
This paper introduces a some good examples of digital games freely available on the web that can be used as educational tools supporting entrepreneurship, innovation and creativity skills b an evaluation framework for identifying such examples. To this end, in the first part of the paper, indicative examples are provided for digital games purposed for entertainment and/or learning, drawn from the broad array of online available business games. In the second part of the paper, the examples provided are evaluated along three dimensions: a generic dimension related to digital-games based learning (DGBL) aspects; and two more specific dimensions, focused on the innovation/creativity and entrepreneurship skills that can be encouraged (and gradually exercised and learnt) through gameplay. The final objective of this evaluation is twofold: firstly, to locate similarities, differences, strengths and weaknesses of the games currently available, that can help identify specific needs for digital games-based entrepreneurial learning material; and secondly, to provide a set of findings and issues that need to be considered while developing (or repurposing) digital games for entrepreneurial learning.